2017
DOI: 10.1177/2378023117736994
|View full text |Cite
|
Sign up to set email alerts
|

Rich Friends, Poor Friends: Inter–Socioeconomic Status Friendships in Secondary School

Abstract: The author examines friendships between students from different socioeconomic groups, investigating the factors that make these relationships more likely and comparing these relationships with those between students from different races, which have been studied more extensively. Consistent with previous research, the results reveal that student homogeneity is positively related to social interaction in schools but that these relationships are not always straightforward with regard to socioeconomic status. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…However, given that low-SES students are least likely to participate in extracurriculars (Pedersen & Seidman, 2005), schools need to reduce typical barriers that prevent such involvement (e.g., cost, transportation). Malacarne (2017), for example, found that living more than one mile from school decreased the odds that a low-SES student would play sports by 28%, while it had no significant effect among higher SES students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that low-SES students are least likely to participate in extracurriculars (Pedersen & Seidman, 2005), schools need to reduce typical barriers that prevent such involvement (e.g., cost, transportation). Malacarne (2017), for example, found that living more than one mile from school decreased the odds that a low-SES student would play sports by 28%, while it had no significant effect among higher SES students.…”
Section: Discussionmentioning
confidence: 99%
“…Extending past research highlighting the resources adolescents acquire from their families at home (Bowen, Chingos, & McPherson, 2009), the current study considers adolescents' close friendships as one potential resource that may help reduce achievement differences related to parental education. Consistent with past research based on Add Health (Malacarne, 2017), cross-class friendship is defined as mutual tie between two students whose parents vary in their level of education (e.g., no high school diploma vs. college degree; some college vs. graduate degree). For this study, we compare students with at least one cross-class friendship at the end of their first year in middle school to those This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Current Studymentioning
confidence: 99%
“…To achieve positive intergroup benefits through extracurricular activities, various groups of students need equal access. For example, low-income students are less likely to participate in extracurricular activities compared to their peers from wealthier homes (Pedersen & Seidman, 2005), particularly if they live farther away from their school (Malacarne, 2017). Steps such as providing transportation (e.g., bus passes if public transportation is available) and limiting outof-pocket expenses (e.g., engaging in group fundraising activities for necessary materials) are critical to equalize access.…”
Section: Promote Shared Goals Outside Classroom Contextmentioning
confidence: 99%
“…The topology of empirical social networks exhibits salient and universal features that can serve as stylised facts to validate artificial graphs. These include the small-world property which holds across many different domains (Galaskiewicz 2007;Newman 2001;Uzzi & Spiro 2005;Weeden & Cornwell 2020), homophily in tie-formation, especially for economic class (Boucher 2015;Cepić & Tonković 2020;Huckfeldt 1983;Malacarne 2017;Mayer & Puller 2008) and their sparsity, especially when focusing on close ties (Mac Carron et al 2016;De Giorgi et al 2020). Schulz et al (2021) present a model of homophilic tie formation that can generate these stylised facts of empirical graph topologies as well as being able to replicate all the relevant findings on positional self-assessment and perceptions of inequality.…”
Section: Related Literaturementioning
confidence: 99%